2004
DOI: 10.1111/j.1469-8137.2004.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium, zinc and substrate heterogeneity on yield, shoot metal concentration and metal uptake by Brassica juncea: implications for human health risk assessment and phytoremediation

Abstract: 313 ResearchBlackwell Publishing, Ltd.Effect of cadmium, zinc and substrate heterogeneity on yield, shoot metal concentration and metal uptake by Summary• Heavy metal contaminants are usually heterogeneously distributed in soils. However, their effects on plants are usually studied under homogeneous conditions. Here we examined the effects of Cd, Zn, and their spatial distribution on shoot yield, shoot metal concentrations, and total metal uptake by Brassica juncea .• One Cd concentration and three Zn concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 52 publications
4
28
0
3
Order By: Relevance
“…It has been reported that B. juncea does not have high Cd accumulating ability when grown in Cd-contaminated soils (Podar, Ramsey, and Hutchings 2004). Our study also showed low Cd accumulation in shoots of B. juncea as well as P. sachalinense under soil culture conditions (Fig.…”
Section: Soil Culture Experimentssupporting
confidence: 70%
“…It has been reported that B. juncea does not have high Cd accumulating ability when grown in Cd-contaminated soils (Podar, Ramsey, and Hutchings 2004). Our study also showed low Cd accumulation in shoots of B. juncea as well as P. sachalinense under soil culture conditions (Fig.…”
Section: Soil Culture Experimentssupporting
confidence: 70%
“…Em condições tropicais a deficiência de zinco é muito freqüente e, no Brasil, também tem limitado a produtividade de algumas culturas (PRADO et al, 2008;TEIXEIRA et al, 2008). A presença de Zn no substrato de cultivo também reduz a absorção de cádmio em Brassica juncea, metal pesado carcinogênico (PODAR et al, 2004). …”
Section: Resultados E Discussão Resultados E Discussão Resultados E Dunclassified
“…Dentre os macronutrientes, N e P são os que mais interferem na produtividade dessas plantas, mas elas também são exigentes em Ca e S, sendo o K e o N retirados do solo em maiores quantidades (FURLANI et al, 1978;SHARMA, 2008). Em função dessa capacidade extratora as brássicas estão sendo testadas com sucesso para detectar metais pesados em substratos diversos, sendo candidatas à fitorremediação (HAN et al, 2004;PODAR et al, 2004;LINDBLOM et al, 2006;LI-XIAN et al, 2007;QI-TANG et al, 2007). Brassica napus L. acumula grandes quantidades de Fe, Mn, Zn, As, Cr, Ni, Cu, Pb, Co, Mo, Cd, Ag e Tl na raiz, mas a transferência desses metais para a parte aérea das plantas é limitada e para as sementes mais ainda, o que garante sua qualidade como fonte de alimento humano (MESTEK et al, 2007).…”
Section: Introdução Introdução Introduçãounclassified
“…Earlier Studies [53,[12][13][14] reported that the effect of heterogeneity of Cd and Zn in soil on plant biomass and uptake. Findings from this study suggest that predictions of plant uptake and plant performance for use in phytoremediation and risk assessment from homogeneous pot trials may not be accurate representations of plant uptake and performance under field conditions, which are usually heterogeneous to some extent.…”
Section: Discussionmentioning
confidence: 99%